Design of 2-amino-6-methyl-pyrimidine benzoic acids as ATP competitive casein kinase-2 (CK2) inhibitors using structure- and fragment-based design, docking and molecular dynamic simulation studies. Issue 3 (4th March 2023) - Patel, S.; Patel, S.; Tulsian, K.; Kumar, P.; Vyas, V.K.; Ghate, M.
ABSTRACT: Overexpression of casein kinase-2 (CK2) has been implicated in several carcinomas, mainly lung, prostate and acute myeloid leukaemia. The smaller nucleotide pocket compared to related kinases provides a great opportunity to discover newer ATP-competitive CK2 inhibitors. In this study, we have employed an integrated structure- and fragment-based design strategy to design 2-amino-6-methyl-pyrimidine benzoic acids as ATP-competitive CK2 inhibitors. A statistically significant four features-based E-pharmacophore (ARRR) model was used to screen 780, 092 molecules. Further, the retrieved hits were considered for molecular docking study to identify essential binding interactions. At the same time, fragment-based virtual screening was performed using a dataset of 1, 542, 397 fragments. The identified hits and fragments were used as structure templates to rationalize the design of 2-amino-6-methyl-pyrimidine benzoic acids as newer CK2 inhibitors. Finally, the binding interactions of the designed hits were identified using an induced fit docking (IFD) study, and their stability was estimated by a molecular dynamics (MD) simulation study of 100 ns.